A boy with developmental delay and mosaic supernumerary inv dup(5)(p15.33p15.1) leading to distal 5p tetrasomy - case report and review of the literature - Tesner, Pavel; Drabova, Jana; Stolfa, Miroslav; Kudr, Martin; Kyncl, Martin; Moslerova, Veronika; Novotna, Drahuse; Kremlikova Pourova, Radka; Kocarek, Eduard; Rasplickova, Tereza; Sedlacek, Zdenek; Vlckova, Marketa (Molecular cytogenetics, 2018)
Background: With only 11 patients reported, 5p tetrasomy belongs to rare postnatal findings. Most cases are due to small supernumerary marker chromosomes (sSMCs) or isochromosomes. The patients share common but unspecific symptoms such as developmental delay, seizures, ventriculomegaly, hypotonia, and fifth finger clinodactyly. Simple interstitial duplications leading to trisomies of parts of 5p are much more frequent and better described. Duplications encompassing 5p13.2 cause a defined syndrome with macrocephaly, distinct facial phenotype, heart defects, talipes equinovarus, feeding difficulties, respiratory distress and anomalies of the central nervous system, developmental delay and hypotonia. Case presentation: We present a boy with dysmorphic features, developmental delay, intellectual disability and congenital anomalies, and a mosaic sSMC inv dup(5)(p15.33p15.1). He is the fourth and the oldest reported patient with distal 5p tetrasomy. His level of mosaicism was significantly different in lymphocytes (13.2%) and buccal cells (64.7%). The amplification in our patient is smaller than that in the three previously published patients but the only phenotype difference is the absence of seizures in our patient. Conclusions: Our observations indicate that for the assessment of prognosis, especially with respect to intellectual functioning, the level of mosaicism could be more important than the extent of amplification and the number of extra copies. Evaluation of the phenotypical effect of rare chromosomal aberrations is challenging and each additional case is valuable for refinement of the genotype-phenotype correlation. Moreover, our patient demonstrates that if the phenotype is severe and if the level of sSMC mosaicism is low in lymphocytes, other tissues should be tested.